Stent–graft repair of carotid endarterectomy–related pseudoaneurysm - Manuela Carnini (Journal of Acute Disease, 2013)
Objective: Carotid endarterectomy-related pseudoaneurysms are rare lesions challenging to be treated with conventional open surgery. Endovascular stent-graft has been rarely adopted with encouraging results. We present a case of a huge carotid pseudoaneurysm treated with a stent-graft and managed with a stent-graft and reviewed the available literature on the management and results of this technique for these challenging lesions.